A power disturbance observer-based sliding mode frequency controller for grid-forming converters - Weiyu Wang; Gongping Wu; Fei Ke; Ye Cai; Jiajun Li; Zhilin Yang; Yijia Cao; Yunfeng Li (International Journal of Electrical Power & Energy Systems)
Grid-forming converters (GFMs) can enable power electronics to mimic the inertia response of synchronous generators (SGs), which can enhance the frequency stability of the ac grids with high penetration of renewable energy sources (RESs). However, GFMs potentially induce oscillations during frequency support because of the similar external dynamics with SGs. In this paper, a power disturbance observer-based sliding mode frequency controller (PDOSMFC) is proposed to facilitate flexible frequency support and enhance system damping through GFMs. By leveraging the intrinsic ability of GFMs to respond to power disturbances in ac grids autonomously, we designed a power disturbance observer to estimate the internal state variables and the external power disturbance using only the local measurements from GFMs. With the estimates of disturbance and states, a modified super-twisting sliding mode control is employed to compensate for the power disturbance to achieve accurate and flexible frequency support. The proposed PDOSMFC is validated via two test systems in a PowerFactory-MATLAB co-simulation environment. The simulation results verified the external power disturbance estimation performance and the frequency support performance.